2017
DOI: 10.1159/000481237
|View full text |Cite
|
Sign up to set email alerts
|

Detection of High-Grade Pancreatic Intraepithelial Neoplasia without Morphological Changes of the Main Pancreatic Duct over a Long Period: Importance for Close Follow-Up for Confirmation

Abstract: Pancreatic intraepithelial neoplasia (PanIN) is a microscopic papillary noninvasive lesion arising from the pancreatic ductal epithelium. However, the natural history and time to progression of high-grade PanIN remain unclear. Herein, we report 2 cases of high-grade PanIN without morphological changes of the main pancreatic duct (MPD) over relatively long periods. In the first case, a 63-year-old man was identified with MPD dilation. Magnetic resonance cholangiopancreatography showed localized stenosis in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Regarding this time window for five years, Yachida et al [ 24 ] reported the duration between the birth of cancer cells and metastasis could be estimated an average of 6.8 ± 3.4 years. Moreover, Yamao et al [ 25 ] and Kuruma et al [ 26 ] reported that CIS developed in patients without morphology change of MPD for a long time (2.1 years and 4.0 years, respectively). These previous studies support the view that our exclusion criteria for time window in pathologically-unproven benign MPD stenosis could be valid.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this time window for five years, Yachida et al [ 24 ] reported the duration between the birth of cancer cells and metastasis could be estimated an average of 6.8 ± 3.4 years. Moreover, Yamao et al [ 25 ] and Kuruma et al [ 26 ] reported that CIS developed in patients without morphology change of MPD for a long time (2.1 years and 4.0 years, respectively). These previous studies support the view that our exclusion criteria for time window in pathologically-unproven benign MPD stenosis could be valid.…”
Section: Discussionmentioning
confidence: 99%
“…No effective strategies for detecting early-stage PDAC are established. Recent advances in imaging modalities, including contrast-enhanced computed tomography (CECT), magnetic resonance imaging (MRI), and endoscopic ultrasonography (EUS), allow for the observation of pancreatic CIS [5][6][7][8][9][10][11][12] and the potential detection of indirect imaging findings such as main pancreatic duct (MPD) dilatation, branch duct dilatation, substantial atrophy, and fat substitution of the pancreatic parenchyma for early diagnosis. Screening of patients with risk factors associated with PDAC, such as family history, hereditary pancreatitis, intraductal papillary mucinous neoplasm, diabetes, and smoking [13][14][15][16][17][18][19], will also enhance early detection.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent genetic and experimental study suggests that transformation of high-grade pancreatic intraepithelial neoplasia (PanIN), a pre-cancerous lesion of PC, into invasive PC required a time period ranging from 3 to 5 years [5]. A few cases have been published in which definite early PC had developed during a long observation period after the initial detection of main pancreatic duct (MPD) stenosis [6,7]. Although these case reports strongly suggested a long-term onset of early PC, estimation of the tumor Diagnostics 2021, 11, 1858 2 of 14 progression time is very difficult because of the small number of reported patients being diagnosed with early PC.…”
Section: Introductionmentioning
confidence: 99%